Reactivation of Tumor-like Chagas Disease in the Central Nervous System in Cardiac Transplant Patients: A Case Series and Literature Review - Prates Júnior, Antônio Gilson; Macedo, Fernando Augusto Medeiros Carrera; Malheiros, José Augusto; Pinheiro, Maria Letícia Marques; Souza, Lucas Rodrigues de; Pinto, Ana Luisa Ribeiro; Pohlmann, Bruna Kelren Freitas (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2023)
Introduction Chagas disease is an important public health problem in Latin American countries, affecting ∼ 6 million people within the region. In patients with chronic Chagas disease who undergo some type of immunosuppression reactivation of the acute form may occur, and manifestations involve many organs, including the central nervous system. Tumor-like brain reactivations are well described in patients with acquired immunodeficiency syndrome; however, this is a very rare event among Chagasic patients immunosuppressed after a heart transplantation.Case Report We describe three cases of cardiac transplant patients who had a tumor-like intracranial lesion, whose biopsies were compatible with Chagas disease. All 3 patients were treated with benznidazole, and 2 of them presented parameters of cure after 60 days of treatment, while 1 required a 2nd cycle of treatment.Discussion A tumor-like Chagas disease reactivation in the central nervous system may happen in heart-transplant patients and, due to the multiple differential diagnoses, we believe that brain biopsies should be considered when feasible.
Keywords: Chagas disease; central nervous system diseases; heart transplantation; immunosuppression therapy